2006
DOI: 10.1080/14756360600741925
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane modulates the activity of glyceraldehyde 3-phosphate dehydrogenase

Abstract: The mechanism of inhalation anesthesia remains to be fully elucidated. While certain neuronal membrane proteins are considered sites of action, cytosolic proteins may also be targets. We hypothesize that inhaled anesthetics may act via glyceraldehyde 3-phosphate dehydrogenase (GAPDH), which has recently been shown to participate in neuronal inhibition. We examined the effects of sevoflurane, a halogenated ether anesthetic, on the catalytic and fluorescence properties of GAPDH. Initial rates of oxidoreductase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…We previously observed that sevoflurane inhibited the activity of GAPDH [4]. In this study, we also observed that isoflurane decreased the activity of GAPDH (Figure 1(a)) in the absence of ULVs.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We previously observed that sevoflurane inhibited the activity of GAPDH [4]. In this study, we also observed that isoflurane decreased the activity of GAPDH (Figure 1(a)) in the absence of ULVs.…”
Section: Discussionsupporting
confidence: 83%
“…GAPDH's binding to the cytoplasmic domain of the α-subunit of the GABA A receptor may be involved in the assembly and trafficking of the receptor. We previously demonstrated that volatile anesthetics affect GAPDH structure and function [3,4], findings that are consistent with those from other studies [5,6]. We propose that the binding of anesthetic agents to GAPDH may contribute to the effect of GAPDH on the GABA A receptor, particularly those involving membrane dynamics.…”
Section: Cis-golgisupporting
confidence: 89%
See 2 more Smart Citations
“…We previously showed that inhaled anesthetics do not sequester proteins, separate from water and remain in liquid form on the bottom of the test vessel due to its density (1.52 g/cm 3 ) [15]. In the current study aqueous ABP was exposed to two interfaces, which we hypothesized may affect ABP conformation and aggregation.…”
Section: Discussionmentioning
confidence: 72%